The Moderating Effect of Supportive Leadership on Green HRM, Green Behavior, and HR Performance - Pangeran; Mhd. Andi Rasyid (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Environmental concerns have prompted organizations to integrate sustainability into human resource practices, yet the implementation of environmentally focused practices in Indonesia’s public sector remains limited. This study aims to investigate the effect of environmentally oriented human resource management practices on employees’ green behavior and performance, with supportive leadership examined as a moderating variable. Data were collected from employees of the Central Bureau of Statistics in North Sumatra Province using a ten-point Likert-scale survey and analyzed through structural equation modeling. The findings reveal that environmentally oriented human resource management significantly enhances both green behavior and employee performance. Green behavior also contributes to improved performance, serving as a key mechanism linking sustainable human resource practices with work outcomes. Additionally, supportive leadership strengthens the impact of these practices by fostering environmental responsibility and employee engagement. The study underscores the theoretical relevance of environmentally focused human resource management in Indonesia’s public sector and highlights the critical role of leadership in promoting sustainability. Structured environmental programs, transparent communication, and reward systems are recommended to cultivate a culture of environmental responsibility.